Performa Stock Parental Udang Galah Dari Muara Sungai Barito, Kintap Dan Pagatan Sebagai Tetua Pada Sistem Seleksi Induk Unggul Lokal - Yulius Kisworo; Mukhlisah Mukhlisah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2015)
This research aimed to obtain parental stock Performa the freshwater prawns from the Barito river, Kintap and Pagatan parent selection criteria in order to obtain a local superior. This research uses experimental methods and design to use Completely Randomize Design 3 treatments and 3 replications. The Results analysis of variance showed different genetic sources provide significant effect on parental sotck performance indicators for the relative growth rate and feed conversion with the highest relative growth derived from genetic resources Br (Barito) with a value of 157.98% and 63.26% for long. Then followed the genetic source Br with relatively heavy growth of 132.92% and 55.82% standard length and the latter originated from genetic resources is to heavy Ki 112.23% and 49.47% standard length, then feed conversion ratio (FCR) ranged between 2.64 -3.59, with the best feed conversion value generated genetic resources parental stock candidates prawns from Barito (Br) and the results of measurements of water quality is still in the normal range and support for the survival of prawns.